Gramicidin A accumulates in mitochondria, reduces ATP levels, induces mitophagy, and inhibits cancer cell growth. Issue 25 (9th June 2022) - Xue, Yun-Wei; Itoh, Hiroaki; Dan, Shingo; Inoue, Masayuki
Abstract : Here we revealed the spatiotemporal behavior of gramicidin A in cancer cells. Gramicidin A depolarizes both the plasma and mitochondrial membranes, inhibits ATP synthesis, and induces mitophagy, thereby causing potent inhibition of cell growth. Abstract : Gramicidin A (1 ) is a linear 15-mer peptidic natural product. Because of its sequence of alternating d - and l -chirality, 1 folds into a β 6.3 -helix in a lipid bilayer and forms a head-to-head dimer to function as a transmembrane channel for monovalent cations (H +, Na +, and K + ). The potent anticancer activity of 1 was believed to be mainly attributed to the free ion diffusion across the plasma membrane. In this study, we investigated the cytostatic action of 1 in nanomolar concentrations using the human breast cancer cell line MCF-7, and revealed the unprecedented spatiotemporal behavior of 1 for the first time. Compound 1 not only disrupted the ion concentration gradients of the plasma membrane, but also localized in the mitochondria and depolarized the inner mitochondrial membrane. The diminished H + gradient in the mitochondria inhibited ATP synthesis. The resultant mitochondrial malfunction led to mitophagy, while the cellular energy depletion induced G1 phase accumulation. The multiple events occurred in a time-dependent fashion and ultimately caused potent inhibition of cell growth. The present study provides valuable information for the design and development of new cytostatic agents exploiting channel-forming natural products.